PENGEMBANGAN MODUL MATEMATIKA SMP BERBASIS PENDEKATAN KONSTRUKTIVISME - Jazim Jazim; Rahmad Bustanul Anwar; Dwi Rahmawati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2016)
The aim of this study was to develop a module of mathematics at the junior high school level class VIII. It is based on the observation of books or teaching materials used in schools is an informative and not involve students in the learning process. This study develops a mathematical module VIII Junior High School class-based constructivism. Constructivism approach chosen by reason will lead students in finding and independently formulate a mathematical concept. This type of research is the development of research (Research and Development), which is intended to develop modules Junior High School math class VIII-based constructivism. This research subject is class VIII student at Junior High School 2 Metro, Junior High School 4 Metro and Junior High School 6 Metro. When the study for two years in which the first year to implement the development of modules and the second year of implementing use of modules developed and seen the results of student learning.  Implementation of the research in the first year has been implemented which reached the stage of expert validation and testing of the small scale of the development of junior high school math module VIII class-based constructivism